Replacement of Fishmeal By Fish Silage in Litopenaeus Vannamei Diets in Biofloc System: Growth Performance and Shrimp Quality - Silva Ribeiro, Felipe de Azevedo; Soares Neto, Joaquim da Rocha; Gonçalves, Alex Augusto; Coelho Emerenciano, Maurício Gustavo (Facultad de Ciencias Biologicas, 2015)
The aim of this study is to evaluate the tilapia silage as alternative protein source in diets for Litopenaeus vannamei reared in clear-water and biofloc conditions. The experiment was performed in a “macrocosm-microcosm” device consisting of two individual systems: biofloc and clear-water. The trial used forty 40L rectangular bins in a density of 63 shrimp/m2. The juveniles were distributed in a bi-factorial completely randomized experimental design with four replicates to each treatment. The treatments were based on the percentage of silage inclusion (control, 1.5, 3.0, 4.5 and 6.0% of inclusion) in biofloc or clear-water based system, totalizing ten treatments. Survival were not affected by both system and diet and stayed above 80% in all treatments. Shrimp mean final weight and SGR was statistically influenced by system (p<0.01) but not by the diet, presenting high values in biofloc condition. Shrimp quality was not affected by diet. Replacement of fishmeal by fish silage in L. vannamei diets is a good option regarding to shrimp production and quality.